Development and effectiveness of ADDIE-based case-based learning model enhancing motivation, critical thinking, and outcomes - Hardin Hardin; Hairuddin Safaat; Lestari Lorna Lolo (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Psychiatric nursing education remains largely teacher-centered, resulting in low student motivation, limited engagement, and suboptimal critical thinking. Innovative, student-centered approaches are needed. This study aimed to develop and evaluate the effectiveness of an ADDIE-based Case-Based Learning (CBL) model in improving learning motivation, critical thinking, and cognitive learning outcomes among nursing students. Research Methodology: This study employed a Research and Development design using the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). A total of 38 fifth-semester nursing students participated. Instruments included an ARCS-based motivation questionnaire, case-based essay tests for critical thinking, and multiple-choice tests for cognitive learning outcomes. Data were analyzed using descriptive statistics and paired-samples t-tests with α = 0.05. Results: Significant improvements were observed across all variables. Learning motivation increased from 64.00 to 70.98 (mean difference = 6.98; t (37) = 14.96; p < 0.001). Critical thinking scores improved from 59.61 to 67.45 (mean difference = 7.84; t (37) = 12.58; p < 0.001). Cognitive learning outcomes increased from 62.72 to 72.32 (mean difference = 9.60; t (37) = 13.55; p < 0.001). These results indicate statistically significant improvements following the implementation of the ADDIE-based CBL model. Conclusion: The ADDIE-based CBL model is valid, practical, and effective in enhancing student motivation, critical thinking, and learning outcomes in psychiatric nursing education. This model supports the adoption of student-centered learning strategies to improve educational quality and readiness for clinical competency.